2020
DOI: 10.1186/s13014-020-01718-w
|View full text |Cite
|
Sign up to set email alerts
|

Phase I trial of dose-escalated stereotactic radiosurgery (SRS) boost for unfavorable locally advanced oropharyngeal cancer

Abstract: Background and purpose Patients with locally advanced oropharynx squamous cell carcinoma have suboptimal outcomes with standard chemoradiation. Here, we evaluated toxicity and oncologic outcomes of dose escalation using radiosurgical boost for patients with unfavorable oropharynx squamous cell carcinoma. Materials and methods Between 2010–2017, Thirty four patients with intermediate- or high-risk oropharynx squamous cell carcinoma were enrolled ont… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…In addition, the results suggest a potential effect of dose escalation on local control. The acute radiation toxicity in the cohort was comparable to the results reported in other published studies [ 7 , 17 , 18 , 22 ] using different radiotherapy techniques and doses. No acute CTCAE grade 4 toxicity manifested.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In addition, the results suggest a potential effect of dose escalation on local control. The acute radiation toxicity in the cohort was comparable to the results reported in other published studies [ 7 , 17 , 18 , 22 ] using different radiotherapy techniques and doses. No acute CTCAE grade 4 toxicity manifested.…”
Section: Discussionsupporting
confidence: 86%
“…One patient discontinued treatment earlier due to non-compliance and a worse tolerance of radiation toxicity. In contrast, Zeno et al [ 17 ] reported an incidence of acute grade 3 dermatitis, mucositis, and dysphagia of 15%, 15%, and 40% during treatment of T2–T4 oropharyngeal, laryngeal, and hypopharyngeal cancer by a combination of EBRT and stereotactic boost. Al-Mamgani et al [ 22 ] reported acute radiation toxicity grade 3 dysphagia in 17–20% of patients treated for oropharyngeal cancer with a combination of EBRT and brachytherapy or stereotactic boost.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The subjective analysis of dysgeusia can be performed by questionnaires where patients report any daily taste changes. The severity of the taste dysfunction can be graded using several intensity scales [11,23,25,30]. Moreover, there are several H&N disease-specific QOL questionnaires, such as the University of Washington QOL Questionnaire (UW-QOL), Functional Assessment of Cancer Therapy-H&N (FACT-H&N), the European Organization for Research and Treatment of Cancer QOL Questionnaire-H&N module (EORTC-H&N35) and 14-item Oral Health Impact Profile (OHIP-14).…”
Section: Dysgeusia Detection Methodsmentioning
confidence: 99%
“…The mild alterations accounted for 56% and 65% of acute and tardive toxicities, respectively, whereas moderate dysgeusia was reported in 32% and 24% of acute and late toxicities, respectively. Despite a gradual return to baseline scores, moderate dysgeusia was experienced by 7% of patients at 24 months post-treatment [23]. In recent years, the use of intensity-modulated RT (IMRT) has allowed for effectively reducing radiation doses.…”
Section: Radiation Therapymentioning
confidence: 99%